Decolonizing Legal Norms: An Examination of Colonial-Era Criminal Codes in Modern Indonesian Jurisprudence - Md Shodiq; Baran Akbulut; Hale Yilmaz (Rechtsnormen: Journal of Law, 2025)
Background. Indonesian criminal law continues to reflect colonial legacies inherited from the Dutch Wetboek van Strafrecht. Despite constitutional independence and ongoing legislative reforms, many colonial-era criminal provisions remain operative and influential within contemporary judicial reasoning, raising critical questions about the depth of legal decolonization in modern Indonesian jurisprudence. Purpose. This study aims to examine how colonial-era criminal codes persist and function within modern Indonesian jurisprudence, with particular emphasis on judicial interpretation, doctrinal practices, and the epistemic continuity of colonial legal norms in criminal adjudication. Method. A qualitative doctrinal and socio-legal research design is employed. The study analyzes statutory criminal law provisions, selected judicial decisions, and relevant legal scholarship using a postcolonial legal theory framework to identify patterns of colonial normative persistence and interpretive reasoning. Results. The findings reveal that a substantial number of criminal law provisions applied in Indonesian courts originate from colonial legal frameworks and are interpreted through formalistic reasoning that prioritizes state authority and public order. Judicial practice demonstrates limited engagement with socio-historical context judicial decisions, and relevant legal Conclusion. The study concludes that legal decolonization in Indonesia remains largely symbolic at the textual level and has not fully transformed jurisprudential practice.